A framework for allocating conservation resources among multiple threats and actions. Issue 5 (28th April 2021) - Moore, Joslin L.; Camaclang, Abbey E.; Moore, Alana L.; Hauser, Cindy E.; Runge, Michael C.; Picheny, Victor; Rumpff, Libby
Abstract: Land managers decide how to allocate resources among multiple threats that can be addressed through multiple possible actions. Additionally, these actions vary in feasibility, effectiveness, and cost. We sought to provide a way to optimize resource allocation to address multiple threats when multiple management options are available, including mutually exclusive options. Formulating the decision as a combinatorial optimization problem, our framework takes as inputs the expected impact and cost of each threat for each action (including do nothing) and for each overall budget identifies the optimal action to take for each threat. We compared the optimal solution to an easy to calculate greedy algorithm approximation and a variety of plausible ranking schemes. We applied the framework to management of multiple introduced plant species in Australian alpine areas. We developed a model of invasion to predict the expected impact in 50 years for each species‐action combination that accounted for each species' current invasion state (absent, localized, widespread); arrival probability; spread rate; impact, if present, of each species; and management effectiveness of each species‐action combination. We found that the recommended action for a threat changed with budget; there was no single optimal management action for each species; and considering more than one candidate action can substantially increase the management plan's overall efficiency. The approximate solution (solution ranked by marginal cost‐effectiveness) performed well when the budget matched the cost of the prioritized actions, indicating that this approach would be effective if the budget was set as part of the prioritization process. The ranking schemes varied in performance, and achieving a close to optimal solution was not guaranteed. Global sensitivity analysis revealed a threat's expected impact and, to a lesser extent, management effectiveness were the most influential parameters, emphasizing the need to focus research and monitoring efforts on their quantification. Abstract : Article impact statement : Accounting for multiple threats and mutually exclusive management actions improves effectiveness of resource allocation. Abstract : Un Marco de Referencia para Asignar Recursos para la Conservación entre Múltiples Amenazas y Acciones Resumen: Los administradores de tierras deciden cómo asignar recursos entre múltiples amenazas que pueden abordarse por medio de múltiples acciones. Adicionalmente, estas acciones varían en viabilidad, efectividad y costo. Buscamos proporcionar una manera para optimizar la asignación de recursos para abordar varias amenazas cuando están disponibles muchas opciones de manejo, incluyendo opciones mutuamente excluyentes. Con una formulación de la decisión como un problema combinatorio de optimización, nuestro marco de referencia toma como entradas el impacto esperado y el costo de cada amenaza para cada acción (incluyendo hacer nada) y para cada presupuesto generalizado identifica la acción óptima a realizar ante cada amenaza. Comparamos la solución óptima con una aproximación de un algoritmo avaricioso fácil de calcular y una variedad de esquemas plausibles de clasificación. Aplicamos el marco de trabajo al manejo de múltiples especies de plantas introducidas en las áreas alpinas de Australia. Desarrollamos un modelo de invasión para predecir el impacto esperado en 50 años para cada combinación de especie‐acción que consideró el estado actual de invasión para cada especie (ausente, localizada, ampliamente distribuida), la probabilidad de invasión, la tasa de esparcimiento, el impacto, cuando abundante, de cada especie y la efectividad de manejo de cada combinación especie‐acción. Descubrimos que la acción recomendada para una amenaza cambia con el presupuesto, que no existe una acción única de manejo óptimo para cada especie y que considerar más de una acción candidata puede incrementar sustancialmente la eficiencia general del plan de manejo. La solución aproximada (solución clasificada por rentabilidad) tuvo un buen desempeño cuando el presupuesto fue igual al costo de las acciones prioritarias, lo que indica que esta estrategia sería efectiva si el presupuesto está fijado como parte del proceso de priorización. Los esquemas de clasificación variaron en cuanto a desempeño, y lograr una solución cercana a lo óptimo no estuvo garantizado. El análisis de sensibilidad global reveló que el impacto esperado de una amenaza y, a menor grado, la efectividad del manejo no fueron los parámetros con mayor influencia, lo que enfatiza la necesidad de enfocar la investigación y los esfuerzos de monitoreo en la cuantificación del impacto esperado y la efectividad del manejo.